Targeting a Novel ER/HOXB7 Signaling Loop in Tamoxifen-Resistant Breast Cancer - Heideman, Marinus R; Frei, Anna; Hynes, Nancy E (Cancer discovery, 2015)
The majority of patients with breast cancer present with an estrogen receptor-positive (ER(+)) tumor, and the endocrine agent tamoxifen is a mainstay for their treatment. Unfortunately, however, resistance remains a major problem because most patients who respond eventually have a recurrence. Thus, an enduring challenge in the breast cancer field is to identify mechanisms underlying tamoxifen resistance. Jin and colleagues describe a novel ER/HOXB7 signaling loop in tamoxifen-resistant breast cancer models. Importantly, they reveal that targeting this signaling loop has great promise as an approach to treat patients with tamoxifen-resistant breast cancer.